2015
DOI: 10.1039/c4ra15632c
|View full text |Cite
|
Sign up to set email alerts
|

One-step hydrothermal synthesis of flowerlike MoS2/CdS heterostructures for enhanced visible-light photocatalytic activities

Abstract: Herein, we report flowerlike MoS 2 /CdS heterostructures prepared by a simple hydrothermal method. The structure and morphology of products are characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The experimental results indicate that the as-prepared products show a flowerlike nanostructure with size at 800 nm. This flowerlike nanostructure has a large surface area and may provide a better anchoring surface for adsorbing molecules. Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 46 publications
(90 reference statements)
1
24
0
Order By: Relevance
“…After forming the MoS 2 /TiO 2 heterostructures, the diffraction peaks of TiO 2 did not shift, while the diffraction peaks of MoS 2 were not obviously observed in the XRD (Figure b). The weak peaks of MoS 2 indicated that the MoS 2 nanosheets have few layers and were too thin to be detected by XRD, which was well consistent with the HRTEM image and previous reports …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…After forming the MoS 2 /TiO 2 heterostructures, the diffraction peaks of TiO 2 did not shift, while the diffraction peaks of MoS 2 were not obviously observed in the XRD (Figure b). The weak peaks of MoS 2 indicated that the MoS 2 nanosheets have few layers and were too thin to be detected by XRD, which was well consistent with the HRTEM image and previous reports …”
Section: Resultssupporting
confidence: 92%
“…As a result, nanosized MoS 2 with exposed edges should be more active for photocatalysis than materials in bulk forms . Recently, some alternative cocatalysts based on few layered MoS 2 nanomaterials have been developed . For instance, Chen et al reported enhancement of the photocatalytic H 2 production activity of CdS by loading transition‐metal dichalcogenide nanosheets as cocatalyst; Xiang et al reported improvement of photocatalytic activity of TiO 2 nanoparticles with the help of MoS 2 and graphene; Zhou et al have synthesized MoS 2 nanosheet‐coated TiO 2 nanobelt heterostructures which exhibit high photocatalytic hydrogen production even without the noble metal co‐catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…This combination allows a rapid charge separation due to different energy level forms of each semiconductor 121 . Several studies have been developing various combinations such as MoS 2 /RGO composites, 122 MoS 2 nanosheets supported by TiO 2 / g ‐C 3 N 4 photocatalysts, 123 ZnO‐MoS 2 ‐RGO heterostructure, 124 MoS 2 /BiOBr microspheres, 125 and flower‐like MoS 2 /CdS heterostructures 126 …”
Section: Tmds‐ws2 and Mos2mentioning
confidence: 99%
“…The heterojunctions of 2D MoS 2 with other low-dimensional TMO&Cs have also been widely investigated. Popular candidates include TiO 2 [ 56 , 69 , 70 , 142 , 143 ], CdS [ 144 , 145 ], ZnS [ 146 ], MoO 3 [ 112 ], ZnO [ 147 ] and CuS [ 148 ]. The detailed photocatalytic performances are shown in Tables 1 , 2 , 3 , 4 , 5 and 6 .…”
Section: Improvement Approach Of Photocatalytic Performances In 2d Trmentioning
confidence: 99%